Word aware : teaching vocabulary across the day, across the curriculum - Branagan, Anna; Parsons, Stephen (Speech therapist) (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Now in a fully updated second edition, this comprehensive and practical book outlines the theoretical underpinnings for vocabulary and acts as a 'how to' guide to developing word learning across the school and curriculum. It is packed with easy-to-implement activities, worksheets and resources that can be put into practice immediately with individual students or groups, whole classes and throughout the school. The Word Aware approach provides a structured approach to promote vocabulary development in all children and has been rigorously tried-and-tested. Now in full colour, with photocopiable and downloadable resources, it is an outstanding resource that will be an essential addition to any school and classroom. The 2nd edition of Word Aware 1 brings: An even wider range of ready-to-go vocabulary activities, Fine-tuned teaching techniques, Enhanced resources to develop children's independent word learning skills, A step-by-step guide to developing a whole school approach Word Aware 1 is an invaluable tool for teachers and other professionals looking to support children as they broaden their vocabulary. It is particularly suited to children aged 5-11 years, but can easily be adapted for older children"--
Keywords: Vocabulary -- Study and teaching (Elementary); Language arts (Elementary); Education, Elementary -- Curricula